Long‐Term Effects of Nusinersen Dosing Frequency on Adult Patients With Spinal Muscular Atrophy: Efficacy of a 6‐Month Dosing Interval - Keita Takahashi; Hitaru Kishida; Misako Kunii; Yosuke Miyaji; Yuichi Higashiyama; Hiroshi Doi; Naohisa Ueda; Hideyuki Takeuchi; Fumiaki Tanaka (Brain and Behavior)
ABSTRACT Objective Spinal muscular atrophy (SMA) is a genetic disease caused by the degeneration of spinal motor neurons due to a deficiency in survival motor neuron protein (SMN) protein, leading to progressive muscle atrophy and weakness. nusinersen, an antisense oligonucleotide that increases SMN protein expression, has shown effectiveness in both pediatric and adult patients with SMA. While it is administrated every 4 months during the maintenance period in most countries, the dosing interval is 6 months in Japan. The impact of this dosing difference on long‐term outcomes is not fully understood. This study evaluates the long‐term efficacy of the 6‐month dosing protocol of nusinersen in adult SMA patients. Methods We assessed 14 adult patients treated with nusinersen every 6 months over a period of up to 39 months using the Hammersmith Function Motor Scale Expanded (HFMSE) and Revised Upper Limb Module (RULM). The results were compared with those from a recent cohort study of adult SMA patients in Europe. Results For ambulatory patients, the mean changes in HFMSE scores at 15, 27, and 39 months were 6.7, 8.3, and 8.0 points, respectively. These results were similar to those observed in the European cohort. In contrast, for nonambulatory patients, the mean changes in HFSME scores were –0.3, –1.4, and –1.3 points, and the mean changes in RULM scores were 2.0, 0.5, and 1.0 points at the same time points. These results were generally less favorable compared to the European cohort but did not reach clinically meaningful deterioration. Discussion The findings of this study suggest that the 6‐month nusinersen dosing protocol provides sustained long‐term benefits for ambulatory adult SMA patients. For nonambulatory patients, the 6‐month protocol appears less effective than the 4‐month protocol. We believe that future nusinersen treatment strategies for adult SMA patients should be flexible, with adjustments based on disease severity. In particular, increasing the dosing frequency and/or dosage in nonambulatory patients may lead to greater improvements.